Mammary gland cytodiagnosis - Arbes, Isabellino; Laviña, Raúl; Pressa, Carlos; Giossa, Walter (Cirugía del Uruguay, 1984)
Mammary gland cytodiagnosis. The authors present lheir experience in cytodiagnosis al the Center of Mammary Gland Diagnosis al Asociación Española Primera de Socorros Mutuos, over a . two-years' period, making special reference to the analysis of secretions and the palpable nodule puncture with a !hin needle.